Radicalization or Reaction: Understanding Engagement in Violent Extremism in Northern Ireland. Issue 2 (15th September 2019) - Ferguson, Neil; McAuley, James W.
Abstract : Over the last decade various theoretical models of radicalization or pathways into engagement in violent extremism have been developed. However, there is a dearth of primary data based on direct contact with violent extremists to test these models. In order to address this weakness, we analyzed accounts of engagement in violent extremism produced by former Northern Irish loyalist and republican paramilitaries to explore their understanding of how and why they engaged in this seemingly politically motivated violence. A thematic analysis incorporating aspects of interpretative phenomenological analysis was employed to gain an understanding of these accounts. While the analysis of the interview transcripts produced findings that share similarities with many of the theoretical models, they challenge the importance of ideological radicalization in fueling initial engagement in violent extremism. Instead, the results demonstrate the importance of collective identity, reaction to events, perceived threats, community grievance, and peer and family influences in fueling initial engagement with the armed groups. Insulation and small‐group pressures within the organizations then amplify identity, threat perceptions, and biases, which increase feelings of efficacy and engagement in violence. Finally, the findings discuss the role of imprisonment in ideologically radicalizing the participants, which in turn allows the paramilitaries to both sustain and rationalize their violent extremism.